2009
DOI: 10.1017/s000711450999208x
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of black v. green tea aqueous extract on hyperglycaemia, hyperlipidaemia and liver dysfunction in diabetic and obese rat models

Abstract: Cardiovascular complications are a major cause of morbidity and mortality in patients with diabetes, obesity and the metabolic syndrome. Recently, there has been an increasing interest in tea as a protective agent against CVD. Here, we compared the modulatory effects of two different doses (50 and 100 mg/kg body weight given orally for 28 consecutive days) of black tea aqueous extract (BTE, rich in theaflavins and thearubigins) and green tea aqueous extract (GTE, rich in catechins) on experimentally induced hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 63 publications
3
66
1
4
Order By: Relevance
“…26 The role of lipids in the pathogenesis of insulin resistance (related to obesity and/or diabetes mellitus) is one of the most important pathogenic determinants. 27 There are studies that have used plants for treatment or prevention of hyperlipidemias: soy, 28 green tea, 29 Malpighia emarginata, 30 and Ananas comosus. 2 Tao et al 31 showed significant reduction in glycemia, cholesterol, and triglycerides by using a traditional antidiabetic formula prepared with many plants.…”
Section: Discussionmentioning
confidence: 99%
“…26 The role of lipids in the pathogenesis of insulin resistance (related to obesity and/or diabetes mellitus) is one of the most important pathogenic determinants. 27 There are studies that have used plants for treatment or prevention of hyperlipidemias: soy, 28 green tea, 29 Malpighia emarginata, 30 and Ananas comosus. 2 Tao et al 31 showed significant reduction in glycemia, cholesterol, and triglycerides by using a traditional antidiabetic formula prepared with many plants.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse beneficial effects to prevent cancer, high cholesterol, allergy and diabetes are also reported. [1][2][3][4] Epigallocatechin gallate (EGCG) is a characteristic constituent of green tea and is known to exert diverse effect of green tea.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the main active components of TP are catechins, known to have important biological and pharmacological properties attributed to their antioxidant properties [10,11,12,13]. Some studies showed TP could scavenge free radicals [10,14], increase the activity of antioxidant enzymes, inhibit lipid peroxidation (LP), and reduce oxidative stress [15], suggesting that TP may combat AGEs formation and diabetic complications.…”
Section: Introductionmentioning
confidence: 99%